2019
DOI: 10.15252/embj.2019101571
|View full text |Cite
|
Sign up to set email alerts
|

Length doesn't matter—telomere damage triggers cellular senescence in the ageing heart

Abstract: Telomere shortening induces cellular senescence in proliferative cells. Yet, it is presently unclear how it is triggered in post‐mitotic cells such as cardiac myocytes. A new study by Anderson et al () reports that during ageing of the heart, cellular senescence develops independently of telomere length, but is evoked by DNA damage, which preferentially accumulates at the telomere. Removal of senescent cells using senolytic drugs ameliorated cardiac hypertrophy and fibrosis and may inform novel approaches to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Different from proliferative cells, post-mitotic cardiomyocytes develop senescent-like phenotypes through a mechanism independent of cell division and telomere length. As characterized by persistent telomeric DNA damage, post-mitotic cardiomyocyte senescence can be mediated by mitochondrial dysfunction, which activates p21 CIP and p16 INK4a , resulting in a non-canonical Senescence-associated secretory phenotype (SASP) [ 70 , 71 ] . Studies revealed the critical role of cardiomyocyte mitochondria in cardiac function [ 72 ] .…”
Section: Telomere Shortening and Dysfunction In Cancer Survivorsmentioning
confidence: 99%
“…Different from proliferative cells, post-mitotic cardiomyocytes develop senescent-like phenotypes through a mechanism independent of cell division and telomere length. As characterized by persistent telomeric DNA damage, post-mitotic cardiomyocyte senescence can be mediated by mitochondrial dysfunction, which activates p21 CIP and p16 INK4a , resulting in a non-canonical Senescence-associated secretory phenotype (SASP) [ 70 , 71 ] . Studies revealed the critical role of cardiomyocyte mitochondria in cardiac function [ 72 ] .…”
Section: Telomere Shortening and Dysfunction In Cancer Survivorsmentioning
confidence: 99%
“…One of the mechanisms of cellular aging is the shortening of telomeres (regions on the ends of chromosomes) [ 196 ]. It happens because of the fact that the region of the chromosome, where the DNA polymerase is located before replication, is not replicated by it.…”
Section: Cellular Types Of Stressmentioning
confidence: 99%
“…After a certain number of divisions, a significant shortening of telomeres occurs and the cell stops dividing. Telomere shortening can contribute not only to the aging of the cell and the whole organism, but also to various diseases [ 196 , 197 , 198 , 199 ]. In particular, Stein, J.Y., et al found that traumatic stress which occurs in soldiers after being captured contributes to the appearing of shorter telomeres [ 197 ].…”
Section: Cellular Types Of Stressmentioning
confidence: 99%
“…To bridge this gap, we recently proposed a model ( Figure 1 ) outlining specific anato-physiological mechanisms relating psychological stress regulation to cellular senescence, and subsequently, age-related pathology ( Ask et al, 2018 ). The model is largely based on the prefrontal component of the central-autonomic network, the immuno reflex (or cholinergic anti-inflammatory pathway; Tracey, 2002 ), and the molecular cell biology related to generation of reactive oxygen species (e.g., Schreck and Baeuerle, 1994 ) and oxidative telomere damage ( Brand, 2019 ; Coluzzi et al, 2019 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both shorter telomeres and increased peripheral levels of inflammation are associated with increased risk for Alzheimer’s disease ( King et al, 2018 ; Wood, 2018 ; Hackenhaar et al, 2021 ). Whether shorter telomeres are a risk for cancer development might depend on cancer type ( Zhu et al, 2016 ), although damage-induced telomere dysfunction can occur irrespective of telomere length ( Victorelli and Passos, 2017 ; Brand, 2019 ). A series of studies associating vagal tone with cancer survival provided some of the first evidence suggesting that vagal modulation of the immune system could be a manner of life and death in clinical conditions ( Mouton et al, 2010 , 2012 ; Chiang et al, 2013 ; De Couck et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%